Acute effects of stretching on flexibility, power and sport specific performance in fencers - Tsolakis, C.; Douvis, A.; Tsigganos, G.; Zacharogiannis, E.; Smirniotou, A. (Journal of Human Kinetics, 2010)
Elite athletes are eager to perform to the best of their ability, regardless of different warm-up stretching techniques used before training or competition which actually help or hinder specific performance variables. The aim of this study was to investigate the acute effects of static or ballistic stretching on flexibility and leg power characteristics of fencing performance in fencers of both genders. Ten male and ten female international level fencers participated in this study. Each subject performed static or ballistic stretching (3 sets of 20 sec) on three muscles of the lower limbs on separate days. Flexibility, squat jump, countermovement jump, drop jump, time and power of lunge and shuttle run test were measured before and after different stretching interventions. Neither static nor ballistic stretching exercises affected flexibility, jumping ability and leg functional fencing performance tests. Moreover, stretching conditions did not affect differently. The results of this study suggest that static or ballistic stretching in the later stages of a general warm-p normally used before training or competition does not hinder specific performance in fencing. Consequently, fencers can continue performing any type of stretching before training or competition at their preference.